Counseling at the intersection: managing work-family conflict among public servants in Malaysia - Puad Mohd Kari, Dharatun Nissa; Mohamed Yusop, Yusliza (Universiti Teknologi Malaysia, 2024)
In Malaysia, the public sector plays a crucial role in the nation’s governance and service delivery. The rising participation of women in the workforce, coupled with evolving societal expectations, has intensified the complexity of managing work and family responsibilities (Abdullah et al., 2021; Goh et al., 2021). The COVID-19 pandemic has further exacerbated this conflict, as remote working and the blurring of boundaries between professional and personal life have become more common (Kasim et al., 2022; Tzafrir et al., 2020). This context presents an opportune moment to explore the role of counseling in addressing work-family conflict among Malaysian public servants. Despite the growing recognition of work-family conflict as a critical issue, there remains a significant gap in research focusing on the counseling strategies used to manage this conflict within the public sector. Previous studies have highlighted the negative impacts of work- family conflict, such as increased stress, reduced job satisfaction, and strained family relationships (Akkaya & Yildiz, 2021; Li et al., 2021). However, less attention has been given to the practical interventions, particularly the role of counselors in supporting public servants through these challenges. This study aims to address this gap by exploring the experiences and strategies of counselors who work with public servants facing work- family conflict. Understanding the counseling approaches that are most effective in this context will contribute to the development of more robust support systems within the public sector.